The Status of Municipal Solid Waste Incineration (MSWI) in China and its Clean Development. (December 2016) - Li, Xinmei; Zhang, Changming; Li, Yize; Zhi, Qiang
Abstract: Many cities in China are facing with a serious crisis of garbage siege. As a major municipal solid waste (MSW) disposal method, the incineration is of great significance to China at present. However, because of the possibility that harmful materials may be emitted into the air and then jeopardize the residents' health, MSWI has encountered strong opposition from the public and therefore, its clean development is necessary. This paper aims to presents a brief review of MSWI technology, energy recovery and utilization as well as emission control in China from the prospect of MSWI's clean development. Firstly, the characteristics and application situation of three major MSWI are summarized. Then, we sum up two main methods of energy recovery and utilization, which are generation of electricity only and cogeneration of heat and power. Finally, some key points of air pollution control and greenhouse gas control are summarized.